Recurrence of anal canal duplication with abscess formation - Mitsuyuki Nakata; Tetsuya Mitsunaga; Elena Terui; Yasuyuki Higashimoto; Jun Iwai (Elsevier, 2018)
Anal canal duplication, a rare congenital disease, is often noticed in fistulas behind the native anus and is sometimes accompanied by abscesses and cysts. The perineal approach and posterior sagittal approach are considered surgical options. A 6-year-old girl with anal canal duplication with abscess formation underwent surgery using the perineal approach but experienced relapse. The foci were completely removed using a posterior sagittal approach, and her condition was cured completely. To prevent the risk of abscess formation, fistulation, and malignancy, it is important to completely remove the fistula/abscess cavity using the posterior sagittal approach during the first treatment or by switching from the perineal approach to the posterior sagittal approach when necessary. Keywords: Anal canal duplication, Abscess formation, Recurrent